1976
DOI: 10.1093/infdis/133.supplement_2.a151
|View full text |Cite
|
Sign up to set email alerts
|

Genital Herpetic Infection in Men and Women: Clinical Course and Effect of Topical Application of Adenine Arabinoside

Abstract: Sixty-three episodes of genital herpetic infection in 55 men and 45 episodes in 42 women were randomly assigned to topical treatment with 3% adenine arabinoside, topical treatment with placebo ointment, or no therapy. In addition, 10 episodes in women who were not randomly assigned to therapy were evaluated and followed. Clinical evaluation and viral cultures were done on day 3, day 8, and weekly thereafter until the lesions had healed. The natural clinical course of genital herpetic infection was defined in p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
12
0
1

Year Published

1978
1978
1983
1983

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(14 citation statements)
references
References 4 publications
1
12
0
1
Order By: Relevance
“…The difference in prognosis for infants of mothers with recurrent infections as compared with those with primary infections may be related to the location and quantity of virus present and to the quantity of maternally derived antibody acquired by the infant. Adams et al found that virus was present on the cervix in 87% of women with primary infections but in only 4% of those with recurrent infections (1). The presence of virus high in the birth canal in contrast to the exterior of the labia majora, the usual site for recurrent lesions, might also influence morbidity, since inoculation of the baby from a labial lesion might occur less often than from a cervical lesion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The difference in prognosis for infants of mothers with recurrent infections as compared with those with primary infections may be related to the location and quantity of virus present and to the quantity of maternally derived antibody acquired by the infant. Adams et al found that virus was present on the cervix in 87% of women with primary infections but in only 4% of those with recurrent infections (1). The presence of virus high in the birth canal in contrast to the exterior of the labia majora, the usual site for recurrent lesions, might also influence morbidity, since inoculation of the baby from a labial lesion might occur less often than from a cervical lesion.…”
mentioning
confidence: 99%
“…The presence of virus high in the birth canal in contrast to the exterior of the labia majora, the usual site for recurrent lesions, might also influence morbidity, since inoculation of the baby from a labial lesion might occur less often than from a cervical lesion. HSV is shed in greater quantities and for longer periods from the cervix by women with primary infections than by those with recurrent infections (1,3).…”
mentioning
confidence: 99%
“…Topical treatment of human genital HSV-2 infections with adenine arabinoside (ara-A) (1,12), or of murine HSV-2 vaginal infection with ara-A or adenine arabinoside 5'-monophosphate (ara-AMP) (16) has been unsuccessful. Topical treatment of mice with either 9-~-D-arabinofuranosylh~oxanthine 5'-monophosphate (ara-HxMP) (2) or phosphonoacetic acid (PAA) (16) did protect mice from lethal vaginal HSV-2 infection.…”
Section: Introductionmentioning
confidence: 99%
“…la) or its more water-soluble derivative, araA-5'-monophosphate (araAMP) (Fig. lb), has not been found to be effective in the topical treatment of either oral or genital herpesvirus infections in humans (1,6,8,14). The most likely explanation for the lack of topical antiviral efficacy in these controlled clinical studies has been suggested to be the failure of these drugs to penetrate the skin.…”
mentioning
confidence: 99%